THE PROBLEM OF LAND RELATIONS IN THE PUBLIC LIFE OF THE KABARDIN-BALKAR REPUBLIC - ATLASKIROV, A.R. (Kavkazologiya, 2019)
The paper discusses the features and problems of the development of land relations in Kabardino-Balkaria. Analysis of the different phases and local variances in the development of land conflicts allows elaborating of their typology. Depending on the object of social collisions, various types of conflicts can be distinguished: agrarian, resident-housing, recreational-rent, ethno-territorial. When looking at the problem in the aspect of the parties or subjects whose interests collide in the land issue, the lines of tension in the land relations lie between the mass of the rural population and the "oligarchic" bureaucratic-business clans; between Balkar villages and large commercial structures; between neighboring Kabardin and Balkar settlements; between organized and unorganized nationalist groups. All the points mentioned above are closely interrelated. In various situations they may either dominate, or sometimes serve as secondary to the others, or sometimes as equal to each other factors affecting the conflict.